Effectiveness of Lecture and Discussion Teaching Methods in Teaching English Language through Figures of Speech - Sharma, Lok Raj; Khanal, Ram Nath (Journal of Advanced Academic Research, 2019)
The main objective of this study is to identify the effectiveness of teaching methods in teaching English language through figures of speech. Thirty-one figures of speech were selected from different prose adverse lines for the study. The study was experimental in nature and the pretest-post test control group research design was adopted among 120 bachelor third year education students from five campuses of Makawanpur District, Nepal. Simple random sampling technique was used to select the students to form the Control Group and the Experimental Group which were taught by using the lecture teaching method and the discussion teaching method respectively for thirty five days. The paired samples t test in SPSS Version 20 was used to compare Total Pretest Mean Score and Total Posttest Mean Score within groups. The overall reliability of the instruments based on the posttest scores of the students of the both groups of the pilot study was .979 and that of the research study was .968. The pair samples t test between the Total Pretest Mean Score and the Total Posttest Mean Score of the Control Group (observed t- value=20.652, critical t- value= 2.001 and p< .05) and the Experimental Group (observed t- value= 42.907, critical t- value= 2.001 and p< .05) show that there was a statistically significant difference between the Total Pretest Mean Score and the Total Posttest Mean Score in each group. It justifies that the lecture teaching method and the discussion teaching method were effective within each group.